2018
DOI: 10.1016/j.trecan.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Reprogramming with IDO1 Inhibitors: Turning Immunologically Unresponsive ‘Cold’ Tumors ‘Hot’

Abstract: We discuss how small molecule inhibitors of the tryptophan catabolic enzyme indoleamine 2,3-dioxygenase (IDOi) represent a vanguard of new immunometabolic adjuvants to safely enhance the efficacy of cancer immunotherapy, radiotherapy or 'immunogenic' chemotherapy by leveraging responses to tumor neoantigens. IDO activation in cancer supports inflammatory processes that IDOi can re-program to help clear tumors by blunting tumor neovascularization and restoring immunosurveillance. Studies of regulatory and effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
116
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(125 citation statements)
references
References 154 publications
(203 reference statements)
0
116
0
Order By: Relevance
“…Indoleamine 2,3‐dioxygenase (IDO), produced within the TME by malignant cells, Tregs, stromal cells, and tolerogenic DCs, converts the essential amino acid tryptophan (Trp) to kynurenine (Kyn) . The lack of Trp results in decreased mTORC1 signaling, activation of the stress kinase GCN2, and triggers cell cycle arrest and apoptosis in effector T cells .…”
Section: Targeting the Tumor Microenvironment To Improve Immunotherapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indoleamine 2,3‐dioxygenase (IDO), produced within the TME by malignant cells, Tregs, stromal cells, and tolerogenic DCs, converts the essential amino acid tryptophan (Trp) to kynurenine (Kyn) . The lack of Trp results in decreased mTORC1 signaling, activation of the stress kinase GCN2, and triggers cell cycle arrest and apoptosis in effector T cells .…”
Section: Targeting the Tumor Microenvironment To Improve Immunotherapiesmentioning
confidence: 99%
“…Furthermore, long-term survival rate after ACT of melanoma-specific pmel TCR transgenic T cells were improved when combined with bicarbonate (40% vs. 10% with ACT alone) [43]. Indoleamine 2,3-dioxygenase (IDO), produced within the TME by malignant cells, Tregs, stromal cells, and tolerogenic DCs, converts the essential amino acid tryptophan (Trp) to kynurenine (Kyn) [44]. The lack of Trp results in decreased mTORC1 signaling, activation of the stress kinase GCN2, and triggers cell cycle arrest and apoptosis in effector T cells [44].…”
Section: Targeting the Tumor Microenvironment To Improve Immunotherapiesmentioning
confidence: 99%
“…Mechanistically, inhibition of IDO1 alone is expected to modulate the microenvironment to potentiate the action of immune effectors, but is not expected to kill tumor cells directly, nor initiate a de novo antitumor immune response (1). In the clinic, IDO1 inhibition alone has little anticancer effect in a majority of patients (6,7). However, early-phase studies demonstrating encouraging response rates and durability of responses suggested that the addition of IDO1 inhibitors to programmed cell death protein 1 (PD-1) or programmed death-ligand 1 (PD-L1) inhibition may enhance the efficacy of checkpoint blockade alone (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Both, tryptophan depletion and increased kynurenine levels, potently inhibit proliferation and are able to induce apoptosis of effector T cells and natural killer cells [41,42]. Of note, high levels of kynurenine generated by IDO1 establish a pronounced immunosuppressive milieu also via the induction and recruitment of immunosuppressive regulatory T cells (Tregs) and myeloid-derived suppressor cells (MDSCs) [43,44]. The potent immunosuppressive role of IDO1 in malignant settings has led to the development of several selective IDO1 inhibitors which are currently tested in clinical trials mainly as ICB adjuvant or pre-clinically in triple combination with radiotherapy [45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Expression of IDO1 is intricately controlled by numerous inflammatory cytokines, often requiring a combination of two signals to reach physiologically relevant levels [39,44,51]. In melanoma, one of the strongest inducers of IDO1 expression is Interferon gamma (IFNγ) via activation of STAT1 [52,53].…”
Section: Introductionmentioning
confidence: 99%